The Development of Balinese Language in Children Aged 5–6 Years in the Balinese Minority Community of Sulawesi Tengah - Galih, Ni Wayan Dina; Ardini, Pupung Puspa; Juniarti, Yenti (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
Preserving the mother tongue is important in building cultural identity, especially in Balinese minority communities outside the area of ​​origin. This study aims to determine the development of the Balinese language of children aged 5–6 years at TK Dharma Santi, Desa Kospa Dwata Karya, Kabupaten Banggai, Sulawesi Tengah. The study used a qualitative approach with observation, interview, and documentation methods. The study subjects included ten children in group B, parents, and class teachers. Data were analyzed using a phenomenological model. The results showed that the development of the children’s Balinese language was quite optimal with five leading indicators: habituation to the use of Balinese, the ability to pronounce simple sentences, understand instructions, participate in conversations, and the use of question words. These findings indicate that school environments contribute to the preservation of the Balinese language from an early age.